Positive Selection within the Schizophrenia-Associated GABA(A) Receptor β(2) Gene - Lo, Wing-Sze (Public Library of Science, 2007)
The gamma-aminobutyric acid type-A (GABA(A)) receptor plays a major role in inhibitory neurotransmissions. Intronic SNPs and haplotypes in GABRB2, the gene for GABA(A) receptor β(2) subunit, are associated with schizophrenia and correlated with the expression of two alternatively spliced β(2) isoforms. In the present study, using chimpanzee as an ancestral reference, high frequencies were observed for the derived (D) alleles of the four SNPs rs6556547, rs187269, rs1816071 and rs1816072 in GABRB2, suggesting the occurrence of positive selection for these derived alleles. Coalescence-based simulation showed that the population frequency spectra and the frequencies of H56, the haplotype having all four D alleles, significantly deviated from neutral-evolution expectation in various demographic models. Haplotypes containing the derived allele of rs1816072 displayed significantly less diversity compared to haplotypes containing its ancestral allele, further supporting positive selection. The variations in DD-genotype frequencies in five human populations provided a snapshot of the evolutionary history, which suggested that the positive selections of the D alleles are recent and likely ongoing. The divergence between the DD-genotype profiles of schizophrenic and control samples pointed to the schizophrenia-relevance of positive selections, with the schizophrenic samples showing weakened selections compared to the controls. These DD-genotypes were previously found to increase the expression of β(2), especially its long isoform. Electrophysiological analysis showed that this long β(2) isoform favored by the positive selections is more sensitive than the short isoform to the inhibition of GABA(A) receptor function by energy depletion. These findings represent the first demonstration of positive selection in a schizophrenia-associated gene.